The Relationship between Peer Support and Adolescents' Adjustment at the Bustanul Ulum Yosowilangun Lumajang Islamic Boarding School - Saputri , Adytia Budi; Zaini , Mad; Komarudin, Komarudin (Universitas Muhammadiyah Jember, 2023)
: Adolescents experience significant changes as a result of the shift from the family environment around their home to the Islamic boarding school environment. They are required to learn to adapt to these changes, so that teenagers can feel comfortable living in the dormitory area. Method: The research design used in this research is Descriptive Correlation using a Cross-Sectional approach . The population of this study were 45 students at the initial level or students of class 1 of junior high school, of which 18 were men and 27 were women. The results of the research show that peer support at the Bustanul Ulum Yosowilangun Lumajang Islamic Boarding School is in the good category , namely 28 teenagers (62.2%) and the adolescent self-adjustment category is sufficient , namely 24 teenagers (53.3%). Results: The results of the Spearman Rho statistical test showed that the value pValue = 0.000 and the value α = 0.05 ( pValue = 0.000 ˂ 0.05), which means that there is a relationship between peer support and adolescent adjustment and there is a strong relationship with the correlation coefficient r = 0.554. Discussion: The success of teenagers in adapting to the Bustanul Ulum Yosowilangun Lumajang Islamic Boarding School influences the adaptation process while at the Islamic boarding school. Future research is expected to develop research with other variables, such as examining factors that influence the adjustment of adolescent students, and examining other sources of support such as support from teachers or family.